Doping of single polymeric nanoparticles. - Zhou, X; Cheng, W; Compton, R (2014)
The oxidative doping of single poly(N-vinylcarbazole) (PVK) nanoparticles is reported in aqueous sodium perchlorate using the nanoimpact method. Complete oxidative doping of single PVK nanoparticles with a size of approximately 120 nm is demonstrated, showing for the first time a simple strategy to synthesize and characterize doped polymeric nanoparticles at the single nanoparticle level.